Fumigation with Muscodor albus volatiles for the control of postharvest decay - Dutra, Deiziane da Consolação (2013)
Postharvest diseases cause considerable losses of fruits and vegetables, from the harvest to their consumption, especially in developing countries. The biological control, particularly by biofumigation, has been pointed as an alternative to reduce postharvest losses. However, for using in the plant disease control, the previous knowledge regarding etiology is essential. A systematic etiological survey was, therefore, conducted in the local market of Viçosa and CEASAMINAS to generate information about the postharvest diseases in Minas Gerais state. The fungi associated with postharvest diseases were isolated, identified and subsequently submitted to in vitro e in vivo tests to verify the potential of Muscodor albus, an endophytic fungus that produces antimicrobials volatiles, in controlling postharvest diseases of fruits and vegetables by biological fumigation. In vitro test was conducted using bipartite Petri dishes with PDA medium, in which M. albus was previously grown for six days in one of the compartments. The mycelial plugs of each pathogen were placed in the other compartment of each plate and cultivated for sixty hours. The M. albus antimicrobial volatiles presented fungistatic or fungicide action depending on the phytopathogenic fungi tested. For the in vivo postharvest micofumigation test, the pathosystem Botrytis cinerea – strawberry was selected because of the in vitro results and the economic importance of gray mold for the crop. Strawberries produced with no pesticides use were wound-inoculated and placed in 11L plastic boxes containing M. albus cultures. The M. albus cultures were grown in Petri dishes containing PDA and the inoculated strawberries were placed in packaging in a way that had no direct contact between fungi and fruits. The micofumigation effectively controlled gray mold and the total decay in postharvest strawberries.